Psychiatric disorder and gynaecological symptoms in middle aged women: a community survey. Issue 6566 (24th January 1987) - Gath, D; Osborn, M; Bungay, G; Iles, S; Day, A; Bond, A; Passingham, C
Abstract : In a community survey 521 women aged 35-59 were selected at random from all patients registered in two groups practices. They were interviewed at home and assessed by means of standardised psychiatric measures and detailed gynaecological inquiry. Levels of psychiatric morbidity were found to be within the expected range for such a sample. Both psychiatric morbidity and the personality dimension of neuroticism were significantly associated with gynaecological symptoms, including dysmenorrhoea and premenstrual tension, some symptoms of excessive menstruation, and flushes and sweats but not disappearance of menstruation for over six months. Current psychiatric state was significantly associated with recent adverse life events and with indices of psychiatric vulnerability (neuroticism and previous psychiatric history), suggesting possible aetiological links with gynaecological symptoms. The findings of this study have implications for the management of gynaecological complaints in general practice.